2016
DOI: 10.1111/bjd.14633
|View full text |Cite
|
Sign up to set email alerts
|

Risk of self-harm and nonfatal suicide attempts, and completed suicide in patients with psoriasis: a population-based cohort study

Abstract: We found limited evidence to suggest an increased risk of self-harm and nonfatal suicide attempts in patients with psoriasis. Importantly, after adjustment for psoriatic arthritis this risk was no longer significantly increased. The risk of completed suicide was also not increased, regardless of psoriasis severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 30 publications
3
61
2
Order By: Relevance
“…A more recent, population‐based cohort from Denmark found no increased risk of self‐harm or non‐fatal suicidal attempt in patients with mild psoriasis (incidence rate ratio (IRR) 1.01, 95% CI 0.17–2.01), but a significantly increased risk in severe psoriasis (IRR 1.69, 95% CI 1.00–2.84), albeit that the result was non‐significant after controlling for PsA. Additionally, they found no increased risk of suicide in mild (IRR 1.05, 95% CI 0.84–1.32) or severe psoriasis (IRR 0.78, 95% CI 0.45–1.36) …”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A more recent, population‐based cohort from Denmark found no increased risk of self‐harm or non‐fatal suicidal attempt in patients with mild psoriasis (incidence rate ratio (IRR) 1.01, 95% CI 0.17–2.01), but a significantly increased risk in severe psoriasis (IRR 1.69, 95% CI 1.00–2.84), albeit that the result was non‐significant after controlling for PsA. Additionally, they found no increased risk of suicide in mild (IRR 1.05, 95% CI 0.84–1.32) or severe psoriasis (IRR 0.78, 95% CI 0.45–1.36) …”
Section: Discussionmentioning
confidence: 96%
“…Patients with a diagnosis of psoriasis were classified into two categories: severe disease if they received a prescription of at least one systemic therapy or phototherapy during the study period and mild disease if they received a code for psoriasis but with no treatment ever recorded, or received only topical treatment during the study period. This classification used to define moderate or severe psoriasis is generally used and has been validated in similar database studies …”
Section: Methodsmentioning
confidence: 99%
“…A population-based study of 57,502 and 11,009 Danish adults with mild and severe psoriasis, respectively, reported 280 patients with suicide attempts and 574 cases of completed suicide. Interestingly, after adjusting for confounding factors, an increased risk of suicide attempts was only seen in severe but not mild cases of psoriasis [13]. A cross-sectional study of 102 patients with psoriasis demonstrated a significant level of stigmatization attributed to their chronic disease [14].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…CHS is the largest managed care organization in Israel, and served a population of about 4 200 000 enrollees during the year 2013 . The magnitude of the CHS databases allows for the assessment of larger patient populations compared with other large‐scale epidemiological studies assessing the prevalence of mental illness in psoriasis patients . The CHS has a comprehensive database with continuous real‐time input from healthcare providers, pharmacies, medical care facilities and administrative computerized operating systems.…”
Section: Methodsmentioning
confidence: 99%